Lärares överväganden kring att leda undervisning - Anja Thorsten; Marcus Samuelsson; Johan Meckbach; Camilla Heiskanen; Anneli Mohlin (Educare)
Previous research describes classroom management as both complex and demanding. Therefore, teachers as leaders need to make many choices about how to handle situations and students. The aim of this study is to describe teachers’ considerations when they are managing the classroom. The study was conducted by a teacher-research team.  The data consist of 12 focus-group interviews with 46 Swedish teachers, spanning from primary to upper secondary school. Through thematic analysis, the following four themes of consideration emerged: (a) control – how much control teachers as leaders should have and how much co-decision that should be given to the students, (b) role – if teachers should be strict or personal, (c) focus – if teachers should focus on the subject or relations to students, and (d) differentiation – if teachers should focus on each individual or on the entire group. This result is an important contribution to understanding the challenges teachers face when managing the classroom and trying to provide learning and development to all students.